Roger Barry Clampitt. (13th January 2018) - Murray, Max; Armour, James; Little, Christopher; Barron, Ronald
Abstract : A clinical pathologist whose outstanding contribution to the profession was to invent the first reliable clinical biochemistry analyser for use in practice.